Accessing industrial site selection criteria by investors in Malaysia - Liaw, Bing Kun (2024)
Malaysia's strategic location in Southeast Asia, coupled with its unique attributes, makes it an attractive destination for Foreign Direct Investment (FDI) and Domestic Direct Investment (DDI). With its central location in the South East Asia, extensive infrastructure, matured highway connection, multiracial population, and robust port facilities, Malaysia stands as an advantageous choice for investors.